Disciplinary Officers and Disciplinary Courts for judges - Bernaciński, Łukasz (Finding a way out of Poland’s rule-of-law crisis: Possible courses of action and reform, 2026)
Chapter Three describes the unlawful dismissal of the Disciplinary Commissioner for Judges of Ordinary Courts and his deputies by the Ministers of Justice after December 13, 2023. The author points out that the law only allows the minister to appoint commissioners, providing no legal basis for their dismissal. Despite this, new appointees and the prosecutor's office forcibly seized disciplinary case files, ignoring Supreme Court rulings that confirmed the illegality of these actions. As part of corrective measures, the author demands that all actions taken by the newly appointed commissioners be declared void. The terms of office of the unlawfully removed deputy commissioners at appellate and regional courts should be restored, and cases taken over by ad hoc commissioners must be returned to the lawful commissioner. Furthermore, rulings issued by defectively appointed disciplinary courts should be annulled by operation of law, and the proceedings reopened. In the long term, the author advocates for a reform of the system to remove the Minister of Justice's influence over disciplinary proceedings. They propose establishing a new, fully independent investigative and prosecutorial body, as well as eliminating local disciplinary courts in favor of a single disciplinary court at the Supreme Court.